PBIS – Computer-user Interface for Phenotypic Breed Identification using Scoring-function Methodology - Bhatia , Avnish. K.; Gupta, Pradeep; Jain , Aanand; Sadana , D. K.; Gokhale, S. B.; Bhagat, R. L. (Journal of Livestock Biodiversity, 2025)
This paper presents computer user-interface, viz., Phenotypic Breed Identification System (PBIS) developed for scoring-function methodology devised for animal’s breed identification based on phenotypic traits (Bhatia et al. 2010, Computers & Electronics in Agriculture, 73: 37-43). PBIS has facilities for adding basic information on livestock species, species-wise animal characteristics, breeds and breed descriptors. Users can add and view test animals along with their phenotypic traits. Breed of test animals can be identified by selecting animals, list of traits and list of breeds for comparison. Results of identification are presented as a report containing list of animals, user’s assessment of breed conformation in percentage, system identified breed, list of breeds compared and list of traits.